Pressure Based Comparison of Different Gas Turbine Ground Vortex Flows - Barata, Jorge M M (2015)
The present paper has the previous work of Barata et al in mind and has the purpose of analyzing the behavior of ground vortex flows through several values of height of the engine axis above the ground, diameter of engine intake and inlet airflow velocity using pressure on the ground and in a 3D scale for that.